Estimating lichen biomass in forests and peatlands of northwestern Canada in a changing climate - Ruth Catherine Errington; S. Ellen Macdonald; Natalka A. Melnycky; Jagtar S. Bhatti (Arctic, Antarctic, and Alpine Research, 2022)
Climate warming in the North could lead to lichen decline within critical woodland caribou habitat. We used repeat measurements of sixty-nine plots over ten years (2007–2008 and 2017–2018) to assess lichen biomass changes under a warming climate along a latitudinal/climatic gradient in northwestern Canada. We compared lichen biomass on sensitive landscape features, including peat plateaux (permafrost-containing bogs), areas of permafrost thaw within the peat plateaux (collapse scars), and low-productivity upland forests occurring on mineral soils. Field-based measures of lichen cover and height were coupled with samples of lichen biomass to develop biomass prediction equations. The optimal model incorporated both cover and height, with landscape feature as a covariate. Although height significantly improved the equation fit, models were successfully developed with cover alone. Modeled lichen biomass differed significantly between landscape features, declining from peat plateau (502 g m−2) to upland forest (54.0 g m−2) and collapse scar (0.690 g m−2) environments. In the absence of permafrost collapse at any monitoring location, lichen biomass declined significantly over the ten years for peat plateaux (−75.6 g m−2) and upland forests (−17.5 g m−2). These results will be important for quantifying landscape-level lichen biomass changes under climate warming in boreal and subarctic environments.